Efektivitas Discovery Learning untuk Meningkatkan Kemampuan Inferensi dan Penguasaan Konsep Kesetimbangan Kimia - Amini, Zelda Amini; Efkar, Tasviri Efkar; Sofya, Emmawaty Sofya (Jurnal Pendidikan MIPA, 2018)
The effectiveness of discovery learning to improve inferencetion skill and mastery concept of chemical equilibrium. The goal of this research was describe the effectiveness of discovery learning model to improve inferencetion skill and mastery concept of chemical equilibrium. This research used quasi experimental method with a pretest-postest control grup design. Sampling was performed by using purposive technique with all of the 11th grade student in SMA Negeri 15 Bandar Lampung as population. This research used two classes as control and experimental class which they were obtained from XI MIA 3 and XI MIA 2 of academic year 2018-2019. The effectiveness of discovery learning was showed by the significant difference of n-Gain between control and experiment classes. The size associated with using effect size. The result obtained size of influence is great. The result of hypothesis testing showed that discovery learning model was effective to improve inferencetion skill and mastery concepts of chemical equilibrium.Keywords: chemical equilibrium, discovery learning model, inferencetion skill, and mastery concepts. DOI: http://dx.doi.org/10.23960/jpmipa/v19i1.pp50-61